TEACHING RESEARCH METHODOLOGY - THEORY, METHODS, PRACTICE: THE CASE FOR ENGLISH LANGUAGE MASTER PROGRAMME - Elena V Voevoda (Peoples' Friendship University of Russia (RUDN University), 2018)
The article considers the use of teaching methods in research methodology class for Master students doing the course in English. The author aims at defining the role and significance of the course in teaching Master students at Moscow State Institute of International Relations (University) and sets the following objectives: to identify conceptual barriers in perceiving research methodology, work out the algorithm of work aimed at building research skills of Master students; analyze the results of pilot teaching. The research methods used in working at the paper are as follows: questionnaire and analysis (in analyzing the results of pilot teaching and content analysis of the methodological part of several Master and PhD open access theses). The author uses activity and competence based approach in the combination with the didactic principles of visualization, systematization, consistency and accessibility. The paper analyzes the requirements of State Federal Education Standards in part of developing the research component of professionally relevant competences. The author identifies cognitive difficulties of perceiving theoretical and methodological material; builds the algorithm of work with conceptual apparatus offering a number of exercises aimed at forming research competence and creating simulation research discourse.